The Effect of Local Cultural Dietary Educational Videos on Dietary Self-Efficacy of Type-2 Diabetes Mellitus Patients in the Village - Pramesti Dwi Agista; Diana Tri Lestari; Yulisetyaningrum Yulisetyaningrum (Journal of Economics and Public Health, 2026)
Diabetes Mellitus (DM) is a non-communicable disease with high prevalence and requires proper dietary management. One important factor in the success of dietary management is patient self-efficacy. However, conventional dietary education is often considered boring, especially in rural communities. This study aims to analyze the effect of a local cultural dietary management education video on improving dietary self-efficacy in type 2 DM patients in Bategede Village. The study design used a quasi-experimental design with a control group pre-test post-test. The study sample used a purposive sampling method of 38 respondents [R1.1] who were divided into an intervention group (19 respondents) and a control group (19 respondents). The instrument used was the Diabetes Management Self-Efficacy Scale (DMSES). Data analysis was carried out using univariate and bivariate statistical tests according to data distribution with the Shapiro-Wilk test. Based on the results, there was a significant difference in self-efficacy between the intervention and control groups, with p = 0.000 (p < 0.05). This confirms that the local cultural dietary management education video is more effective in improving self-efficacy than without intervention.